1997
DOI: 10.1136/hrt.77.3.238
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity after His bundle ablation and rate response ventricular pacing for drug refractory chronic atrial fibrillation.

Abstract: Objective-To evaluate exercise capacity of patients with chronic atrial fibrillation in whom His bundle ablation followed by ventricular rate response pacing (WIR) was carried out because of drug refractoriness. Design-Prospective study. (1) angina pectoris of more than New York Heart Association (NYHA) class II (IV), (2) aortic or mitral valvar stenosis or incompetence, (3) respiratory diseases interfering with normal oxygen uptake, (4) any other abnormality interfering with the capability of performing a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1998
1998
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 15 publications
(4 reference statements)
1
7
0
Order By: Relevance
“…These values were significantly lower in our study population (compared to healthy age‐matched adults as reported in ref. ) at baseline and demonstrated substantial increase after successful ablation, suggesting that preserved atrial contraction or a regular rhythm or both, are critical to maintain cardiac output and exercise performance . Our result was in agreement with an earlier study by Gosselink et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These values were significantly lower in our study population (compared to healthy age‐matched adults as reported in ref. ) at baseline and demonstrated substantial increase after successful ablation, suggesting that preserved atrial contraction or a regular rhythm or both, are critical to maintain cardiac output and exercise performance . Our result was in agreement with an earlier study by Gosselink et al .…”
Section: Discussionsupporting
confidence: 93%
“…However, it is still obscure how these alterations are perceived by different individuals, as patients with similar clinical and electrophysiological profiles have been seen to be either symptomatic or asymptomatic . In addition to arrhythmia symptoms, patients with AF often report reduced exercise tolerance, which has been attributed to impairment of the cardiac output response to exercise . Furthermore, AF, symptomatic or silent, is known to affect the quality of life (QoL) adversely …”
Section: Introductionmentioning
confidence: 99%
“…Despite this improved exercise capacity, neither strategy resulted in an improved VO 2 max, which is consistent with previous studies. 3 Twenty four hour Holter monitor at follow up confirmed good overall heart rate control was achieved with either treatment, as the maximum heart rates were similar between the two groups. The mean heart rate was lower in the ablation group compared to the medical group, because of the lower base rate chosen (60 bpm v 70 bpm).…”
Section: Discussionmentioning
confidence: 70%
“…Radiofrequency catheter ablation of the His bundle (or atrioventricular node) and implantation of a rate responsive pacemaker (VVIR pacemaker) has been shown to improve symptoms, quality of life, and exercise duration in patients with permanent atrial fibrillation (AF) and medically refractory fast ventricular response. [1][2][3] Left ventricular function if impaired can also improve following ablation. 2 4-10 This benefit of His bundle ablation (HBA) may be caused by improved ventricular rate control, ventricular rhythm regulation or a combination of both.…”
mentioning
confidence: 99%
“…Case series and randomized trials of AVJ ablation with permanent pacemaker implantation have proven it to be an effective therapeutic option for improving symptoms and quality of life …”
Section: Effectivenessmentioning
confidence: 99%